Was I being critical? Vision and action in English language teacher education - Enrique Alejandro Basabe (Asociación Colombiana de Profesores de Ingles, 2019)
Criticality has recently made its way into the field of English Language Teaching. It has mainly fostered the study of teachers' individual commitments with their social context. A reflective account is offered here based on my praxis when I adopted a critical pedagogy to teach literature in the English language teacher education program at the National University of La Pampa (UNLPam) in Argentina. Drawing on observations and documents, I give in this paper an autoethnographic account of my practice. The results show that I maintained a constant questioning of my practice and a persistent wariness about the appropriateness of keeping a critical position in my teaching context. All teachers should perform these two reflective actions in view of our role as socially and pedagogically responsible agents of practice.